NEEDS ASSESSMENT ON ACTION RESEARCH COMPETENCIES OF TEACHER-RESEARCHERS IN SURIGAO DEL SUR, PHILIPPINES - CORTES, SYLVESTER TAN (Journal of Education and Innovation, 2019)
This study assesses needs of teacher-researchers (n=247) in Surigao del Sur, Philippines which employs cross-sectional, descriptive research design. The preliminary phases of this study were the development and validation of an instrument which examines their competence on action research (AR), and clustering them based on the similarity of their responses through Hierarchical Cluster Analysis. The factor analysis in instrument development yields five competencies in conducting AR, namely: (a) problem identification, (b) data collection, interpretation, action, and reflection, (c) appropriate use of data collection tools, (d) application of technology, and (e) research ethics which total percentage of variance explained is 77.52. Meanwhile, the Cluster Analysis created two clusters of teacher-researchers. Cluster 1 (n=113) perceived themselves proficient in all five competencies while teachers in cluster 2 (n=99) rated themselves proficient in three competencies except in the application of technology and research ethics where they consider themselves advanced. However, these levels still indicate recalibration of competencies to both clusters. In this regard, this study suggests that the capacity building programs on AR organized by their division research office need an alignment with the competencies specified per factor. Further, mass training of teachers should be refrained because they are not of the same level of competence or eventual needs in doing AR.